HUBUNGAN BILATERAL ANTARA INDONESIA DENGAN INDIA - Amelia, Mutiara; Jamaan, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research discusses bilateral relations between Indonesia and India which includes the history of bilateral relations between countries, the look east policy, and the formation of the Indonesia India Comprehensive Economic Cooperation Agreement (CECA) and the ASEAN India Free Trade Area (AIFTA). This research aims to find out how bilateral relations between Indonesia and India were from the beginning of independence to the establishment of trade cooperation. This research uses qualitative methods with library study data collection techniques sourced from journals, theses, official websites, ministry performance reports. The results of this research showed that Indonesia has established bilateral relations with India since 1961, which was marked by a state visit. In particular, India has issued a Look East Policy which has become the foundation for strengthening relations between the two countries. Meanwhile, relations between Indonesia and India have improved in status with the establishment of comprehensive cooperation, namely CECA and AIFTA. Keyword: AIFTA, CECA, Indonesia, India, Trade